The contribution of family physicians in coordinating care and improving access at district hospitals: The False Bay experience, South Africa - Liezel Rossouw; Hoosain Lalkhen; Kaashiefah Adamson; Klaus B. von Pressentin (AOSIS, 2021)
This short report describes three family physicians (FP)-led clinical governance interventions to strengthen the care access and coordination in an urban district hospital in Cape Town, South Africa. The actual experiences and their effects on health services are captured here. The report also describes a range of interventions from enhanced access to timely computer tomographic scans to determine definitive care, to creating a local referral forum between levels of care, which resulted in a renewed appreciation for the scope of services and illness burden managed by the district health system and to the establishment of an onsite echocardiology service at the local district hospital to enhance the identified burden of disease of the local community. Each of these interventions were planned and implemented based on local data in partnership with the team members at the different levels of care. By applying an inclusive and distributed leadership style as informed by care access to scarce resources was better coordinated for the local communities served. The importance of the building trusting relationships between FPs and referral hospital colleagues cannot be overemphasised. Family physicians should be integrated and collaborated in the clinical governance platforms across levels of care. The FP's roles as primary care consultant and clinical governance leader are pivotal in enhancing service delivery efficiency and in providing quality healthcare.